2014
DOI: 10.1186/1471-2431-14-230
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ views on care of their very premature babies in neonatal intensive care units: a qualitative study

Abstract: BackgroundThe admission of a very premature infant to the neonatal intensive care unit (NICU) is often a difficult time for parents. This paper explores parents’ views and experiences of the care for their very premature baby on NICU.MethodsParents were eligible if they had a baby born before 32 weeks gestation and cared for in a NICU, and spoke English well. 32 mothers and 7 fathers were interviewed to explore their experiences of preterm birth. Although parents’ evaluation of care in the NICU was not the aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
109
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 36 publications
8
109
0
16
Order By: Relevance
“…Our findings from the five families who were interviewed twice suggest this does not change over time; parents at both time points reinforced their need for clear and consistent information using different clinical scenarios to discuss their needs. These findings reflect those of Russell et al 10 and the UK Poppy study,16 who found that parents experienced dissatisfaction and anxiety if they received conflicting information or if they felt that they had gone against the advice of another professional. Our findings provide an important insight into these engagement issues by suggesting that improved communication is required between professionals themselves, regarding treatment plans and previous discussions with parents, in order to help parents feel more comfortable and confident with their baby’s carers.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings from the five families who were interviewed twice suggest this does not change over time; parents at both time points reinforced their need for clear and consistent information using different clinical scenarios to discuss their needs. These findings reflect those of Russell et al 10 and the UK Poppy study,16 who found that parents experienced dissatisfaction and anxiety if they received conflicting information or if they felt that they had gone against the advice of another professional. Our findings provide an important insight into these engagement issues by suggesting that improved communication is required between professionals themselves, regarding treatment plans and previous discussions with parents, in order to help parents feel more comfortable and confident with their baby’s carers.…”
Section: Discussionsupporting
confidence: 87%
“…Constraints on staff limit the time available for extensive parent counselling by physicians, leaving parents to depend on nurses to help explain their infant's status. [8] Reis et al [11] report that interaction with nurses and verbal and written information regarding the condition of infants were essential, and of course the method of communication was also of significance. It has also been observed that excessive information can lead to parental confusion, which therefore can decrease confidence in healthcare systems, increase anxiety and eventually decrease parental satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[8,9] Therefore we planned this study with the objective of assessing parental satisfaction with the traditional system of NICU care in a public sector hospital in North India, and of identifying the areas that need improvement and can be worked upon.…”
mentioning
confidence: 99%
“…The premature birth and subsequent hospitalisation of infants in the Neonatal Intensive Care Unit (NICU) are highly traumatic and distressing events for parents (1) , leading to a breakdown of the family unit due to the impediments, constraints, and situations undermining the family routine (2) . The hospitalisation of a child in the NICU is a difficult and challenging experience for mothers and their families, since the highly modern and technological environment of the NICU separates the babies physically, psychologically, and emotionally from their parents (2)(3) .…”
Section: Introductionmentioning
confidence: 99%
“…Based on this premise, a growing number of studies have used qualitative methods to explore what the health team can do to help parents during the stay of babies in the neonatal unit, and to highlight areas of particular importance for their care (1)(2)9) . Therefore, understanding the feelings and experiences of mothers during the permanence of their babies in intensive care can help the NICU team plan actions and better confront the situation with esteem and safety for the hospitalised infant (4) .…”
Section: Introductionmentioning
confidence: 99%